MENINGKATKAN HASIL BELAJAR IPA SISWA KELAS V MELALUI MODEL KOOPERATIF TYFE NHT (NUMBERED HEAD TOGETHER) DI SDN BOJONGSALAM - Didi, Didi (IKIP Siliwangi, 2021)
This research is based on the low learning outcomes of V students at SDN Bojongsalam. Seeing these problems, it is necessary to improve efforts. The purpose of this study is to describe how the activities of teachers and students, improving learning outcomes and student responses to the cooperative model of NHT time. This study uses a classroom action research method (PTK) which is carried out in two cycles with research procedures that include: planning, implementing piercings, observing, and reflecting. The instruments used in this study included test questions, interviews/field observations, and teacher and student performance instruments. Based on the results of data analysis, it can be concluded that the NHT-type cooperative model can improve student learning outcomes. There was an increase in two cycles in the first cycle of 70% and the second cycle of 82.45%.